Distribution, Emphasis and Possible Interactions among Tourism Research Centres in Mercosul - Pimentel, Thiago Duarte; Costa de Carvalho, Fabíola Cristina; Bifano de Oliveira, Marcela Costa (Anais Brasileiros de Estudos Turísticos, 2016)
The aim of this paper is to presente an overview about the existence and the likely interactions of Tourism Research Centres (TRC) among the Mercosul countries, as a prerequisite of innovations in tourism field. It was used a quantitative and qualitative method of analysis. As a result it was found an asymmetrical distribution of TRC between the countries, with nonspecific emphasis and no relation to each other. In this regard the institutionalization stage of knowledge production in tourism, as a precondition of its development, is still incipient.